2019
DOI: 10.1038/s41419-019-1518-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-induced translocation of GRP78 to the plasma membrane triggers a pro-apoptotic feedback loop in pancreatic beta cells

Abstract: The 78-kDa glucose-regulated protein (GRP78) is an ubiquitously expressed endoplasmic reticulum chaperone, with a central role in maintaining protein homeostasis. Recently, an alternative role for GRP78 under stress conditions has been proposed, with stress-induced extracellular secretion and translocation of GRP78 to the cell surface where it acts as a multifunctional signaling receptor. Here we demonstrate translocation of GRP78 to the surface of human EndoC-βH1 cells and primary human islets upon cytokine e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…GRP78 is an important molecular chaperone that prevents the aggregation of misfolded proteins in the ER 31 , 32 . DNAJC3 is a co-chaperone of GRP78 that attenuates general protein synthesis under ER stress 33 . This revealed that ER also involved in the stress of reduced background radiation.…”
Section: Discussionmentioning
confidence: 99%
“…GRP78 is an important molecular chaperone that prevents the aggregation of misfolded proteins in the ER 31 , 32 . DNAJC3 is a co-chaperone of GRP78 that attenuates general protein synthesis under ER stress 33 . This revealed that ER also involved in the stress of reduced background radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Cell surface GRP78 can be shed and circulating GRP78 levels were found to be increased in subjects with diabetes and obesity and to correlate with CRP levels, suggesting that the chronic inflammation could be a contributing factor to the observed increase in addition to the metabolic stress (151). Indeed, as well as induction by metabolic stress, inflammatory cytokines also appear to stimulate the translocation of GRP78 to cell surfaces (152). Accumulation of AGEs can also induce GRP78 via activation of RAGE (153,154).…”
Section: Glucose-regulated Protein 78 (Grp78)mentioning
confidence: 99%
“…GRP78 can move in under the condition of ER outside the region, even secrete to the outside of the cell with the corresponding ligand binding, playing its function by affecting various signaling pathways, influencing the cell signal transduction and the development (Figure 1). Under certain pathological conditions, cytokines produced by the body, due to exposure to inflammatory environment, promote the surface translocation of GRP78, which further explains the prominent position of GRP78 in many diseases (7). Recent studies have demonstrated that GRP78 has far more functions than this (4,8,9).…”
Section: Introductionmentioning
confidence: 99%